Production of Biofuels and Chemicals with Ultrasound - Fang, Zhen (Springer, 2015)
Conversion of biomass into chemicals and biofuels is an active research and development area as trends move to replace traditional fossil fuels with renewable resources. By integrating processing methods with ultrasound and microwave irradiation into biorefineries, the time-scale of many operations can be greatly reduced while the efficiency of the reactions can be remarkably increased so that process intensification can be achieved. “Production of Biofuels and Chemicals with Ultrasound” and “Production of Biofuels and Chemicals with Microwave” are two independent volumes in the Biofuels and Biorefineries series that take different, but complementary approaches for the pretreatment and chemical transformation of biomass into chemicals and biofuels.